La crianza y educación infantil como cuestión social, política y cotidiana: una etnografía en barrios populares del gran Buenos Aires - Santillán, Laura (2009)
Important advances have been made in the social sciences with respect to our understanding of cultural variation in forms of childrearing and education.  However, common sense and certain academic discourses are persistently reductionist in taking only some aspects of childhood into consideration. In this article I analyze the processes and relations that surround activities related to childcare and education in contexts of marked social inequality.  The analysis is based on ethnographic fieldwork in popular neighbourhoods of Greater Buenos Aires, Argentina. I demonstrate how the socialization and education of children living in poor neighbourhoods are embedded in networks of intervention that depend on diverse social actors that include but also exceed the bounds of the institutions that might be expected to relate to this sector.  These actors, discussed as «social» and «political,» produce meanings that refer to education in its connections to different dimensions of social life, in a framework of social relations that are shot through with power.